2012
DOI: 10.1038/ajg.2011.423
|View full text |Cite|
|
Sign up to set email alerts
|

Serum and Colonic Mucosal Immune Markers in Irritable Bowel Syndrome

Abstract: OBJECTIVES Low-grade colonic mucosal inflammation has been postulated to have an important role in the pathophysiology of irritable bowel syndrome (IBS). The objectives of this study were (i) to identify serum and tissue-based immunological and neuroendocrine markers associated with mucosal inflammation in male (M) and female (F) patients with non-post-infectious IBS (non-PI-IBS) compared with healthy controls and (ii) to assess possible correlations of such markers with IBS symptoms. METHODS Sigmoid mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
133
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 71 publications
(114 reference statements)
4
133
3
1
Order By: Relevance
“…In conclusion, the study by Chang et al ( 22 ) provides another piece of evidence, which supports a state of abnormal immune regulation in IBS. It is attractive to speculate that in aff ected individuals, luminal insults such as enteric infections, dysbiosis, or environmental exposures might serve as the hand that strikes the match to induce low-grade infl ammation, and in some, the symptoms of IBS.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In conclusion, the study by Chang et al ( 22 ) provides another piece of evidence, which supports a state of abnormal immune regulation in IBS. It is attractive to speculate that in aff ected individuals, luminal insults such as enteric infections, dysbiosis, or environmental exposures might serve as the hand that strikes the match to induce low-grade infl ammation, and in some, the symptoms of IBS.…”
mentioning
confidence: 71%
“…Elevated proinfl ammatory cytokines from peripheral blood mononuclear cells in the basal period and aft er stimulation with lipopolysaccharides has been shown in IBS-diarrhea ( 14 ). In contrast, other investigators could from men and women with IBS ( 22 ). Th eir well-characterized IBS population was recruited from a US specialty clinic and the surrounding community.…”
mentioning
confidence: 99%
“…One possibility is to also evaluate patients with colonoscopy and relevant biological markers, as well as obtain a detailed symptom history. 47,49,50 The symptom data can then be compared with the biological markers and colonoscopy results using statistical techniques, such as latent class analysis and Bayesian analysis. 51 These techniques can classify patients into categories based on the underlying structure of the data, without relying on a gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, only a few studies have addressed the association of IL-10 and IL-10 gene polymorphisms in IBS. Chang et al [7] reported lower colonic mucosal mRNA expression of IL-10 in IBS females compared with healthy females. Moreover, several IL-10 genotypes were less prevalent in patients with IBS compared with that of control groups [8].…”
mentioning
confidence: 98%